Treatment of Acetabular Bone Defect in Revision of Total Hip Arthroplasty Using 3D Printed Tantalum Acetabular Augment - Ying, Jiawei; Cheng, Liangliang; Li, Junlei; Wu, Bin; Qiu, Xing; Zhang, Tianwei; Wang, Feng; Liu, Baoyi; Yang, Lei; Pokharel, Durga Bhakta; Xie, Hui; Wang, Fuyang; et al. (Orthopaedic surgery, 2023)
Objective The treatment of acetabular defects is one of the most difficult challenges of revision of total hip arthroplasty (RTHA), and tantalum is regarded as a promising bone substitute material. This study aims to investigate the effectiveness of 3D printed acetabular augment used in RTHA for the treatment of acetabular bone defect. Methods A retrospective analysis of the clinical data of seven patients who had undergone RTHA was carried out using 3D printed acetabular augment from January 2017 to December 2018. The CT data of the patients were exported to Mimics 21.0 software (Materialise, Leuven, Belgium), and the acetabular bone defect augment were designed, printed and then implanted during operation. The postoperative Harris score, visual analogue scale (VAS) score and prosthesis position were observed to evaluate the clinical outcome. A I‐test was used for preoperative and postoperative comparison of the paired‐design dataset. Results A firm attachment of the bone augment to the acetabulum during operation without any complications was found during the follow‐up time 2.8–4.3 years. The VAS score of all patients was found 6.9 ± 1.4 before operation and was 0.7 ± 0.7 at the last follow‐up (P ≤ 0.001), and the Harris hip scores, were 31.9 ± 10.3 and 73.3 ± 12.8 before operation, and at the last follow‐up (P ≤ 0.001), respectively. Moreover, no loosening sign between the bone defect augment and the acetabulum was observed during the entire implantation period. Conclusion 3D printed acetabular augment is effective in reconstructing the acetabulum following an acetabular bone defect revision, which enhances the hip joint function and eventually makes a satisfactory stable prosthetic. We did a retrospective analysis of the clinical data of seven patients underwent revision of total hip arthroplasty. The 3D‐printed tantalum augment was designed and manufactured for acetabular defect preoperatively. An advantage intraoperative stability and good mid‐term follow‐up were achieved with this method.